Knowledge, use and perceptions of artificial intelligence Chatbots among Italian physiotherapists: an online cross-sectional survey - Deodato, Manuela; Sabot, Raffaele; Galmonte, Alessandra; Palese, Alvisa; Castellini, Greta; Turolla, Andrea; Pillastrini, Paolo; Cook, Chad; Rodeghiero, Lia; Gianola, Silvia; Rossettini, Giacomo (Frontiers in Digital Health, 2025)
IntroductionArtificial Intelligence (AI) Chatbots are increasingly being integrated into healthcare, but little is known about their role in physiotherapy. This study investigated the knowledge and use, perceived benefits, limits, and barriers of AI Chatbots in the Italian physiotherapy community.MethodsA cross-sectional survey was conducted between March and July 2024. Italian physiotherapists, members of the Associazione Italiana di Fisioterapia (AIFI), were invited through mailing lists and social media. Inclusion criteria: AIFI membership, current employment as a physiotherapist, Italian language proficiency, and willingness to participate. A total of 415 out of 2,773 physiotherapists responded (15% response rate); 50.6% were women, and 50.4% had more than 10 years of experience. The survey comprised four sections: (a) respondent characteristics; (b) knowledge and use of AI Chatbots; (c) perception of benefits; and (d) perception of limits and barriers. Descriptive statistics and multivariable logistic regression analyses were performed.ResultsOverall, 93.3% of physiotherapists had heard of AI Chatbots, but 66.9% had never used them in clinical practice. Among those who had, 11.3% reported a “positive” and 14.5% a “very positive” experience. Despite limited use, 78% expressed a positive attitude towards future adoption, and 50% considered AI Chatbots potentially helpful in clinical practice. Reported risks included patient self-diagnosis (84.4%), spread of false information (72.1%), and reduced human interaction (64%). Having more than 21 years of experience was significantly associated with a higher frequency of AI Chatbot use (OR: 5.93, p = 0.013). Age was also a significant predictor of use frequency (OR: 1.05, p = 0.013), with older physiotherapists reporting more frequent AI use.ConclusionItalian physiotherapists acknowledged both opportunities and risks in implementing AI Chatbots. Although current adoption is limited, the overall positive attitude suggests a likely increase in future use. Targeted strategies, including guidelines and educational initiatives, are needed to ensure safe and effective integration into clinical practice.